A REQUIREMENTS ANALYSIS OF PROBLEM UNDERSTANDING OF BIOLOGICAL TEACHERS RELATED TO DEVELOPMENT OF CHARACTER EDUCATION BASED LEARNING - Wahyu, Wahyu; M. Rambitan, Vandalita; Daniel, Daniel (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aims to examine the understanding of biology teachers in class XI Public High School related to the development of character education-based learning tools in the form of syllabus, lesson plans, LKPD, evaluation, and handouts. The research subjects were biology teachers at Public High School 1, Public High School 2, Public High School 3, Public High School 5, Public High School 10 Samarinda. Data collection was carried out by interviewing, distributing questionnaires, observing, documenting. The data obtained were analyzed descriptively and interpretively based on the percentage. Results of the analysis showed understanding relevant biology teacher development role of learning tools based character education It is shown from the results of the analysis to answer questions related to the introduction of character education learning 41.67 percent answered and 58.33 percent did not answer, the application of character education learning 33.33 percent answered and 66.67 percent did not answer, describing the stages of character education learning 16.67 percent answered and 83.33 percent did not answer, the empowerment of character education was 33.33 percent answered and 66, 67 percent did not answer. There are steps taken to improve teacher understanding in applying inquiry learning models by developing valid, practical, effective character education learning tools